2011
DOI: 10.1039/c1cp22520k
|View full text |Cite
|
Sign up to set email alerts
|

Disentanglement of triplet and singlet states of azobenzene: direct EELS detection and QMC modeling

Abstract: Singlet and triplet excited states of trans-azobenzene have been measured in the gas phase by electron energy loss spectroscopy (EELS). In order to interpret the strongly overlapping singlet and triplet bands in the spectra a set of large-scale correlated quantum Monte-Carlo (QMC) simulations was performed. The EELS/QMC combination of methods yields an excellent agreement between theory and experiment and for the two low-lying excited singlet and two low-lying triplet states permitted their unambiguous assignm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 48 publications
2
23
2
Order By: Relevance
“…Our present study as well as our recent many-body study of the AB molecule [53,54] do not support reason a). The many-body study revealed deviations from experiments by as much as ≈1 eV with DFT techniques and even with medium-quality quantum chemistry methods [53,54], depending on the level of correlation and/or basis set used.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our present study as well as our recent many-body study of the AB molecule [53,54] do not support reason a). The many-body study revealed deviations from experiments by as much as ≈1 eV with DFT techniques and even with medium-quality quantum chemistry methods [53,54], depending on the level of correlation and/or basis set used.…”
Section: Discussioncontrasting
confidence: 99%
“…Our present study as well as our recent many-body study of the AB molecule [53,54] do not support reason a). The many-body study revealed deviations from experiments by as much as ≈1 eV with DFT techniques and even with medium-quality quantum chemistry methods [53,54], depending on the level of correlation and/or basis set used. However, these differences affect mostly the singlet/triplet excited states of the molecule [54], rather than the states around the Fermi level responsible for the conductance of the contacted molecule which are very similar for both isomers.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Indeed, this has to be done in a stepwise manner since several sets of parameters enter the multistage approach 37,38 : Table 1 The FN-DMC interaction energies E (kcal/mol) obtained from various tested protocols compared to the CCSD(T)/CBS reference E R (kcal/mol). The protocol-type attribute, if applicable, is indicated in the column P. For clarity, analyzed features of the protocols with respect to the standard 26 3tJ protocol are indicated by the bold typeface.…”
Section: Analysis Of Qmc Protocolsmentioning
confidence: 99%
“…Electron scattering experiments allow an insight into, for example, the electronic structure of molecules (e.g. [2]) as well as enabling the investigation of more fundamental phenomena like quantum coherence [3] and others [4]. From an applied perspective, the requirement to quantify and understand electron-molecule collisions stems from a number of fields and media [5,6]: from astrophysics to both natural and man-made plasmas (used, for example, in industry for microchip production) and processes induced by secondary electrons generated by ionizing radiation incident on biological (e.g.…”
Section: Introductionmentioning
confidence: 99%